2011
DOI: 10.1200/jco.2010.31.8436
|View full text |Cite
|
Sign up to set email alerts
|

Philadelphia-Negative Classical Myeloproliferative Neoplasms: Critical Concepts and Management Recommendations From European LeukemiaNet

Abstract: We present a review of critical concepts and produce recommendations on the management of Philadelphia-negative classical myeloproliferative neoplasms, including monitoring, response definition, first-and second-line therapy, and therapy for special issues. Key questions were selected according the criterion of clinical relevance. Statements were produced using a Delphi process, and two consensus conferences involving a panel of 21 experts appointed by the European LeukemiaNet (ELN) were convened. Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
685
1
36

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 729 publications
(736 citation statements)
references
References 85 publications
9
685
1
36
Order By: Relevance
“…However, familial clustering of PV, ET and PMF has been well described and patients should know that occasionally other members of the family may present these disorders. 16,17 In accordance with the European Leukemia Net (ELN) investigators, 18 in the absence of hematological or clinical abnormalities, I do not routinely genotype for JAK2 mutations or JAK2 46/1 (GGCC) haplotype the relatives of individuals with MPNs. 19 Patients should be notified that follow-up of PV, ET and to lesser extent early/prefibrotic PMF 20 is marked by thrombohemorrhagic complications, constitutional symptoms, such as pruritus, night sweats, fatigue and a propensity to transform into overt myelofibrosis (10 --25%), and acute leukemia (o5%), however, at different incidence concerning the disease entities.…”
Section: How To Diagnose Mpn In Children and Young Adultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, familial clustering of PV, ET and PMF has been well described and patients should know that occasionally other members of the family may present these disorders. 16,17 In accordance with the European Leukemia Net (ELN) investigators, 18 in the absence of hematological or clinical abnormalities, I do not routinely genotype for JAK2 mutations or JAK2 46/1 (GGCC) haplotype the relatives of individuals with MPNs. 19 Patients should be notified that follow-up of PV, ET and to lesser extent early/prefibrotic PMF 20 is marked by thrombohemorrhagic complications, constitutional symptoms, such as pruritus, night sweats, fatigue and a propensity to transform into overt myelofibrosis (10 --25%), and acute leukemia (o5%), however, at different incidence concerning the disease entities.…”
Section: How To Diagnose Mpn In Children and Young Adultsmentioning
confidence: 99%
“…Anagrelide is not licensed as first-line therapy for ET in Europe and the ELN group recommends this drug as second line therapy. 18 The use of aspirin (ASA) in children less than 12 years of age should be prescribed with caution because of the risk of Reye's syndrome. Overall, according to ELN experts, there are insufficient data to recommend a specific agent in children, and the choice should be individually tailored.…”
Section: How To Manage Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with ET have a relatively benign prognosis [2], but thrombotic and hemorrhagic events may indeed occur over time, leading to severe morbidity [3][4][5]. Previous studies by Cortelazzo et al [6][7][8] showed that age [60 years and previous thrombotic or hemorrhagic events are strongly associated with a higher risk of developing further events. Conversely, the socalled low-risk ET group (young patients without previous vascular events), may also develop thrombotic or hemorrhagic events during follow-up.…”
Section: Introductionmentioning
confidence: 99%